Development of Fully Self-Controllable High-Finesse Optical Reference Cavities - Jiao, Dongdong; Wu, Mengfan; Gao, Jing; Zhang, Han; Liu, Junlong; Xu, Guanjun; Zang, Qi; Cui, Jie; Dong, Ruifang; Liu, Tao; Qu, Bo; Zhang, Shougang (Chinese physics letters, 2025)
High-finesse optical reference cavities are essential tools for fundamental research. In response to China’s historical reliance on importing high-finesse optical reference cavities, we successfully developed a cavity using ultralow expansion glass (ULE) materials and processed it entirely in China. Using the method of measuring the cavity linewidth, a finesse of approximately 480000 was obtained in our experiments. We adopted a relatively simple and effective approach to test the optical reference cavity, which involved measuring the resonant points using an ultrastable laser. Remarkably, an expansion coefficient of the Chinese ULE optical reference cavity reached up to the order of 10 −9 /K within the temperature range of 27 °C to 40 °C, with the zero expansion point occurring at approximately 34 °C. These findings demonstrate China’s independent capability to develop high-finesse optical reference cavities, which is a significant advancement in precision optics.